2020
DOI: 10.1177/0030222820950510
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Experiences With Death and Terminal Patients During Clinical Education

Abstract: The aim of this study is to explore nursing students’ experiences with death and terminal patients during clinical education. A secondary analysis of qualitative data that were collected through 11 focus group interviews with nursing students was performed. Data obtained from the interviews were analyzed using thematic analysis. There were a total of 9 themes across 3 contexts. Data were grouped under the following themes: feelings experienced when encountering death for the first time, reactions to the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
4
0
3
Order By: Relevance
“…Proper preparation of mentors and their positive attitude toward students are the key to establishing an educational relationship. According to a study by Bhurtun et al from 2019, vocational teachers and nursing staff are a vital stress factor because students feel constantly watched and evaluated [( 15 ), p. 266–272] Another study confirming the importance of the teacher in the process of student preparation is the study by Gül et al from 2019, where they showed that, according to students, a part of teachers avoids patients and families who are considered terminally ill ( 30 ). According to Gillian et al, students' experiences are primarily shaped by other people, especially experienced nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Proper preparation of mentors and their positive attitude toward students are the key to establishing an educational relationship. According to a study by Bhurtun et al from 2019, vocational teachers and nursing staff are a vital stress factor because students feel constantly watched and evaluated [( 15 ), p. 266–272] Another study confirming the importance of the teacher in the process of student preparation is the study by Gül et al from 2019, where they showed that, according to students, a part of teachers avoids patients and families who are considered terminally ill ( 30 ). According to Gillian et al, students' experiences are primarily shaped by other people, especially experienced nurses.…”
Section: Discussionmentioning
confidence: 99%
“…S. Gül ir kt. (2020) nustatė, kad studentams trūksta teorinių žinių apie paliatyviąją pagalbą, todėl jiems reikia didesnės mentorių ir kitų slaugytojų pagalbos praktikos metu [5]. Galimybė reflektuoti ne tik su mentoriais apie pacientų būklę, bet ir su kitais apie asmeninius, emocinius išgyvenimus susidūrus su mirtimi praktikos metu, padeda formuoti profesinius medicinos studento įgūdžius [12].…”
Section: įVadasunclassified
“…Veriler yüz yüze toplanmış olup form ve ölçeklerin doldurulması ortalama 15 dakika sürmüştür. 17,36 Gallagher ve ark. 'nın yaptıkları bir çalışmada da öğrencilerin yaşam sonu dönem hasta bakımı ile ilgili klinik uygulama öncesinde eğitim aldıklarında sadece hastaya değil ailelerine de daha nitelikli bakım sunulacağı belirtilmiştir.…”
Section: Araştırmanın Uygulanmasıunclassified
“…[14][15][16] Bu çeşitliliği oluşturan durumlar ise öğrencilerin yaşam sonu bakım eğitimi alma, daha önce ölüm olgusuyla karşılaşma ya da ölüme yönelik hissettikleri korku gibi faktörlerle ilgili olduğu belirtilmektedir. 17,18 Hemşirelik öğrencileri klinik uygulamalar esnasında ölümle karşılaşabilmektedir. Aynı zamanda ölüm sürecinde olan hastalar ile karşılaşacakları ve bu hastaların yaşanmışlıkları, öğrencilerin kendi ya da sevdiklerinin ölümlerini hatırlamaya neden olabilmektedir.…”
Section: Introductionunclassified